An experience using different synchronisation mechanisms on a shared memory multiprocessors - Kaya, D (Elsevier Science Inc, 2005)
In this paper, we are concerned with a number of parallel algorithms for comparing three different synchronization mechanisms when applied to a particular problem. The problem is the reduction of a general matrix to upper Hessenberg form. The algorithms were written in C++ programming language using the Encore Parallel Threads [Encore Computer Corporation, Encore Parallel Threads Manual. No. 724-06210 Rev. A, 1988] package using a shared memory MIMD computer. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: parallel algorithms; Hessenberg reduction; C plus plus programming language; The Encore Parallel Threads